The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/sms.14142
|View full text |Cite
|
Sign up to set email alerts
|

Influence of muscle‐belly and tendon gearing on the energy cost of human walking

Abstract: This study combines metabolic and kinematic measurements at the whole‐body level, with EMG and ultrasound measurements to investigate the influence of muscle‐tendon mechanical behavior on the energy cost (Cnet) of walking (from 2 to 8 km·h−1). Belly gearing (Gb = Δmuscle‐belly length/Δfascicles length) and tendon gearing (Gt = ∆muscle‐tendon unit length/∆muscle‐belly length) of vastus lateralis (VL) and gastrocnemius medialis (GM) were calculated based on ultrasound data. Pendular energy recovery (%R) was calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 46 publications
(165 reference statements)
0
19
0
Order By: Relevance
“…We also observed differences in terms of strut function between tasks as a function of speed, which suggests that during walking at speeds > 5.5 km/h the behaviour of the muscle fascicles could be impaired compared to running. This speculation is supported by a recent study of Monte et al [ 8 ], who observed that the operating length of the GM muscle fascicle is, indeed, impaired at high walking speeds.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…We also observed differences in terms of strut function between tasks as a function of speed, which suggests that during walking at speeds > 5.5 km/h the behaviour of the muscle fascicles could be impaired compared to running. This speculation is supported by a recent study of Monte et al [ 8 ], who observed that the operating length of the GM muscle fascicle is, indeed, impaired at high walking speeds.…”
Section: Discussionmentioning
confidence: 62%
“…Sasaki and Neptune [ 6 ], in their modelling study, revealed that running below the transition speed required more muscle fiber work than walking, and, inversely, walking above the transition speed required more muscle fiber work than running. Furthermore, as recently reported by Monte et al [ 8 ], the neuromuscular system is not able to promote “sustainable” GM fascicle mechanics at walking speeds > 7 km/h. This mechanical disadvantage increases the EMG activity required to sustain muscle contraction, increasing the metabolic energy expenditure at the whole-body level.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In healthy subjects, belly gearing was found to play an important role during rapid movements since it is positively correlated with mechanical power production 18 as well as with the capability to increase force rapidly 15 . More recently, it was observed that belly gearing could play a role in determining the metabolic energy demands during walking at increasing speed 39 and this could partially explain the increase in the metabolic demands during walking in PD patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%